Analysis of Acoustic and Perceptual Variables in Three Heritage Churches in Quito Using Structural Equation Modeling - Fausto Espinoza; Luis Bravo-Moncayo; Luis Garzón; Víctor Poblete; Jorge P. Arenas (Buildings)
Acoustic quality is one of the aspects that contribute to the heritage of cultural and religious spaces. It is increasingly common to find scientific literature detailing the sound characteristics of places of worship, especially those with cultural and historical significance. This article presents a comprehensive acoustic characterization of three colonial heritage churches in Quito. It examines the relationship between objective and subjective parameters that influence the valuation of a space or sound environment. To analyze this relationship, we employed structural equation modeling (SEM) to evaluate three latent variables using perceptual acoustic indicators. The SEM results highlighted significant associations between physical acoustic parameters, emotional responses, and evaluative judgments, underscoring that traditional intelligibility metrics alone may not fully capture acoustic quality in these contexts. These findings provide a robust interdisciplinary framework that spans objective measures and human perception, offering valuable guidance for future heritage conservation efforts.